Central Government Responsibility in Mitigating the Impact of Cieunteung Retention Pond Development in Bandung Regency: A Causative Analysis - Shofi Siti Sholihah; Iyep Saefulrahman; Idil Akbar (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2024)
The Cieunteung Retention Pond was constructed in 2015 and completed in 2018 by the central government through BBWS Citarum. Despite this, flooding in Dayeuhkolot and its surrounding areas in Bandung Regency has continued to occur sporadically between 2020 and 2021. This study aims to analyze and describe the government's responsibility, particularly BBWS Citarum, based on J. Spiro's theory of Responsibility. In this theory, Spiro outlines three aspects that influence responsibility, with this research focusing on discussing the issues within the aspect of responsibility as cause. The research uses a qualitative method with data presented descriptively. The findings indicate that BBWS Citarum has successfully met the construction targets but has yet to address new problems that have arisen post-construction due to several factors